Level of IgG antibodies, tumor necrosis factor alpha and T-cell exhaustion in persons vaccinated against SARS-CoV-2 - Lozada Requena, Ivan (2024)
Immunity against COVID-19 is crucial. Little is known about the mechanisms involved in stimulating antibody production against SARS-CoV-2 by the tumor necrosis factor alpha (TNF-α) and the exhaustion of T-cells. Objective: To evaluate the IgG (anti-spike) response, TNF-α, T-cell subsets, and their exhaustion. Methods: Serum samples and peripheral mononuclear cells of subjects with infection (G1, n=07), asymptomatic (G2, n=08 y G3, n=10) vaccinated with three doses of the BNT162b2 (G1 and G2) or the ChAdOx1-S (G3) vaccines. ELISA determined the level of IgG and TNF-α, and flow cytometry determined the T-cell subsets and exhaustion. Results: No change was observed in the levels of IgG before and after vaccination. G1 significantly increased TNF-α levels after receiving the third vaccine dose. Total lymphocytes significantly decreased in G2, but CD3+ did not change. G3 had a reduction in LTCD4+ and an increase in PD-1+, LTCD8+, and PD-1+ before and after the third vaccine dose. A positive correlation was observed after the third vaccine dose in G3 among IgG and CD4+PD-1+(p=0.034) and CD8+PD-1+(p=0.028), respectively. Conclusions: Humoral (IgG) and inflammatory (TNF-α) responses were not modified significantly; the heterologous vaccine (G3) increased levels of CD4+ cells, a subset that sustains antiviral adaptative immunity, and avoids T-cell exhaustion.